2016
DOI: 10.1038/pr.2016.207
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric kidney transplantation: a historical review

Abstract: Successful renal transplantation is the optimal treatment for chronic kidney failure, but this was not always so for children. Beginning with the first kidney transplants in the 1950s, children experienced poorer patient and graft survival rates than adult patients. But over the last 6 decades, an improved understanding of the immune system which has steered pediatric multi-center clinical/pharmacokinetic and mechanistic studies that have sculpted our immunosuppression with markedly better patient and graft su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 78 publications
1
77
0
13
Order By: Relevance
“…First successful kidney transplantation in man was possible in December 23, 1954 . While centers in the west have been practicing pediatric transplantation since 1960s, the exact time of initiation of pediatric transplantation in a developing country is unavailable . Much progress has been achieved in the field of organ transplantation till date.…”
Section: Discussionmentioning
confidence: 99%
“…First successful kidney transplantation in man was possible in December 23, 1954 . While centers in the west have been practicing pediatric transplantation since 1960s, the exact time of initiation of pediatric transplantation in a developing country is unavailable . Much progress has been achieved in the field of organ transplantation till date.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric priority was categorized as pre‐Share 35, Share 35, and KAS. In 2005, Share 35 preferentially allocated organs from deceased donors under 35 years of age to pediatric patients . In 2014, KAS transitioned to priority from donors with a KDPI ≤ 35% .…”
Section: Methodsmentioning
confidence: 99%
“…Recipients without pediatric priority, referred to henceforth as "adults" or "adult recipients," were considered only for the initial analysis comparing utilization between adult and pediatric recipients. 13 In 2014, KAS transitioned to priority from donors with a KDPI ≤ 35%. 5 Finally, the onset of the American opioid epidemic was defined as January 1,…”
mentioning
confidence: 99%
“…10 In contrast, earlier single center publications on steroid avoidance, 11,12 using historical controls, were ranked very highly at #s 8 and 9 on this list-an indication of a positive result publication bias in the list, since the randomized trial only showed equivalence between the two arms, and did not affirm superiority of many metrics of steroid avoidance that were shown in the single center studies. Based on data from the journal websites, from Google Scholar and Web of Science in 2019, many newer papers 13,14 now may have greater than 45 citations of the 200th paper in the…”
mentioning
confidence: 99%